2020
DOI: 10.1002/14651858.cd013101.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic corticosteroids for paediatric heart surgery with cardiopulmonary bypass

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the benefits and harms of prophylactic corticosteroids in children between birth and 18 years of age undergoing cardiac surgery with cardiopulmonary bypass. B A C K G R O U N D Description of the condition Paediatric heart surgery outcomes have improved markedly over time as a result of marginal gains in training, technology and safety systems (Brown 2015; Hoashi 2015; Jacobs 2016; NICOR 2016). This improvement ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…23 A 2020 Cochrane review (13 studies) and a more recent meta-analysis (10 trials) on the topic both concluded that prophylactic corticosteroids probably reduce the length of postoperative hospital length of stay but likely do not alter mortality or overall morbidity after congenital cardiac surgery. 5,29 Limitations and Future Directions Our report, however, has limitations. Source studies consist of a limited number of randomized control trials (RCTs) that are exclusively single-center works with small sample sizes.…”
Section: Suggested Circi Pathwaymentioning
confidence: 83%
See 3 more Smart Citations
“…23 A 2020 Cochrane review (13 studies) and a more recent meta-analysis (10 trials) on the topic both concluded that prophylactic corticosteroids probably reduce the length of postoperative hospital length of stay but likely do not alter mortality or overall morbidity after congenital cardiac surgery. 5,29 Limitations and Future Directions Our report, however, has limitations. Source studies consist of a limited number of randomized control trials (RCTs) that are exclusively single-center works with small sample sizes.…”
Section: Suggested Circi Pathwaymentioning
confidence: 83%
“…18,22,24 Two recent meta-analyses echoed these observations, finding the most benefit in neonates and surgeries with STS risk score >3. 5,23 2. Clinical criteria: Table 2 shows general criteria for hemodynamic instability.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 233 reviews and protocols. We excluded 197 records because they did not focus on mechanically ventilated patients and finally included 36 records [17–51]. See the flow diagram in Figure 1.…”
Section: Resultsmentioning
confidence: 99%